LANDSCAPE EVALUATION OF MOSQUE GARDEN BASED ON THE CONCEPT OF ISLAM - Tafliha, Isnaeni Nur (Journal of Islamic Architecture, 2020)
Islam is a religion that has a comprehensive concept. It regulates everything in the Muslim's life because everything is connected with Islam, including designing a garden. This paper discusses the textual concept of the garden in Islam based on the Al-Quran and al-Hadith as the two primary sources in Islam. The textual analysis aims to formulate garden design criteria based on the concept of Islam. The design criteria were then used to evaluate the mosque's landscape by studying perceptions and user preferences. The two selected mosque locations are the Istiqlal Mosque and the Jakarta Islamic Center Mosque. The method applied in this study is a literature study and the distribution of questionnaires. The paper's results and discussion are divided into three parts: 1) garden design criteria based on the Al-Quran and al-Hadith; 2) some sharia limitations in designing the garden; 3) evaluation on two research locations through the study of perceptions of mosque garden users.Â Â